CHD7 mutations in patients initially diagnosed with Kallmann syndrome – the clinical overlap with CHARGE syndrome - Jongmans, MCJ (2008)
Kallmann syndrome (KS) is the combination of hypogonadotropic hypogonadism and anosmia or hyposmia, two features that are also frequently present in CHARGE syndrome. CHARGE syndrome is caused by mutations in the CHD7 gene. We performed analysis of CHD7 in 36 patients with KS and 20 patients with normosmic idiopathic hypogonadotropic hypogonadism (nIHH) in whom mutations in KAL1, FGFR1, PROK2 and PROKR2 genes were excluded. Three of 56 KS/nIHH patients had de novo mutations in CHD7. In retrospect, these three CHD7-positive patients showed additional features that are seen in CHARGE syndrome. CHD7 mutations can be present in KS patients who have additional features that are part of the CHARGE syndrome phenotype. We did not find mutations in patients with isolated KS. These findings imply that patients diagnosed with hypogonadotropic hypogonadism and anosmia should be screened for clinical features consistent with CHARGE syndrome. If such features are present, particularly deafness, dysmorphic ears and/or hypoplasia or aplasia of the semicircular canals, CHD7 sequencing is recommended.